Modelling and sizing a grid-connected PV-battery system using DIgSILENT for powering UTeM main campus - Gan, Chin Kim; Tan, Pi Hua; Qaid, Khaldon Ahmed; Tee, Wei Hown (Gazi Universitesi, 2023)
Universities encounter challenges stemming from the escalating electrical bills attributed to the substantial energy consumption of their expansive buildings. This serves as a clear impetus for universities to transition to renewable energy technologies, which offer the advantages of cost-effective operation and minimal environmental footprint. This paper presents the design of a grid-connected photovoltaic (PV) system with battery storage to fulfil the electricity consumption needs of Universiti Teknikal Malaysia Melaka (UTeM) main campus. The objective is to reduce grid dependency, lower electricity costs, and minimize carbon dioxide (CO2) emissions. The system was modelled and simulated using DIgSILENT software. Load demand and energy consumption data were extracted from the Tenaga Nasional Berhad (TNB) electricity bill, while the PV profile and irradiance data were obtained from the UTeM solar laboratory. Based on the findings, it has been determined that a 12 MWp PV system, coupled with a 25.8 MWh battery, represents the optimal solution for satisfying the total electricity demand of UTeM's main campus. The installation of this system is projected to result in estimated monthly electricity bill savings of MYR 422,611 for UTeM. Furthermore, the proposed system offers a significant environmental benefit by potentially reducing CO2 emissions by up to 1,507,520 kg per month. The findings of this study can inform decision-makers in implementing a costeffective and environmentally friendly energy solution for UTeM's main campus.